2013
DOI: 10.1016/j.ssresearch.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant background peer effects in Italian schools

Abstract: This article provides an empirical assessment of the effect of immigrant concentration on student learning in Italian primary and lower secondary schools, using the data of a standardized learning assessment administered in 2010 to the entire student population of selected grades at the national level. Identification is accomplished by exploiting the within-school random variability observed in the share of immigrant students across classes. I estimate peer effects allowing for heterogeneous effects between na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…On the other hand, many studies have found either no (Cebolla-Boado and Garrido Medina, 2011 ; Agirdag et al, 2012 ) or even negative effects (Stanat, 2006 ; Verwiebe, 2013 ) of higher proportions of migrants in the classroom or in the school on all students' performance. However, the majority of past research revealed a negative effect of the proportion of migrants on academic outcomes for specific migrant groups (Westerbeek, 1999 ; Fekjær and Birkelund, 2007 ; Contini, 2013 ). Drawing on the findings of negative composition effects on performance of migrants, we postulate that an increase in the proportion of migrants will be negatively related to migrant students' performance.…”
Section: Ethnic Classroom Composition Effects On Performancementioning
confidence: 99%
“…On the other hand, many studies have found either no (Cebolla-Boado and Garrido Medina, 2011 ; Agirdag et al, 2012 ) or even negative effects (Stanat, 2006 ; Verwiebe, 2013 ) of higher proportions of migrants in the classroom or in the school on all students' performance. However, the majority of past research revealed a negative effect of the proportion of migrants on academic outcomes for specific migrant groups (Westerbeek, 1999 ; Fekjær and Birkelund, 2007 ; Contini, 2013 ). Drawing on the findings of negative composition effects on performance of migrants, we postulate that an increase in the proportion of migrants will be negatively related to migrant students' performance.…”
Section: Ethnic Classroom Composition Effects On Performancementioning
confidence: 99%
“…1 Three more recent papers focus specifically on the Italian experience by analysing administrative data on the standardized INVALSI test in primary and lower secondary schools. Two of these, relying on within-school variation in immigrant concentration, find that the proportion of immigrant students has a weak negative effect on child learning outcomes that is either slightly larger for children from low socio-economic background (Contini, 2013) or highly non-linear (Tonello, 2016). In contrast, Ballatore, Fort and Ichino (2018), by exploiting class formation rules to identify the causal impact on native test scores of increasing the number of immigrants in a classroom while keeping class size and student quality constant, find sizable negative effects on native performance in both literacy and maths at ages 7 and 10.…”
Section: Introductionmentioning
confidence: 99%
“…They find no spillover effects of immigrant students to native British students. Contini () presents evidence from Italy finding that the estimated spillover effects are generally negative, although the size of these effects are small and heterogeneous. The concentration of first‐generation immigrants has a small negative effect on the natives’ test scores and those who are affected the most are the children from the lowest socioeconomic background.…”
Section: Introductionmentioning
confidence: 99%